2008
DOI: 10.1097/nmd.0b013e3181775f05
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between PTSD Arousal Symptoms and Depression Among Mothers Exposed to the World Trade Center Attacks

Abstract: Posttraumatic stress disorder (PTSD) is associated with greater risk of developing comorbid depression. However, little is known about the relationship between specific PTSD symptom clusters and comorbid depression. Approximately 4 years after the World Trade Center (WTC) attacks, we examined the association between PTSD symptom clusters and depression severity among 64 mothers directly exposed to the WTC attacks. Severity scores were computed for each PTSD symptom cluster by summing symptom frequency. Partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
8
0
4
Order By: Relevance
“…In this study, PTS was not a main predictor, but used as a control variable to better distinguish the predictors that had a unique effect on the level of depressive symptoms. Further, the symptom overlap often found between PTSD and depression pertains mainly to the arousal symptom cluster (Rubacka et al ., 2008), and not the intrusion symptoms included in the present study. A further limitation is the few response alternatives, restricting the ability to control for intensity of the intrusive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, PTS was not a main predictor, but used as a control variable to better distinguish the predictors that had a unique effect on the level of depressive symptoms. Further, the symptom overlap often found between PTSD and depression pertains mainly to the arousal symptom cluster (Rubacka et al ., 2008), and not the intrusion symptoms included in the present study. A further limitation is the few response alternatives, restricting the ability to control for intensity of the intrusive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewed studies show that MDD is not always concurrent with PTSD and suggest that, consistent with previous studies carried out after other traumatic events [52,53], both disorders can be considered related but different posttraumatic reactions. In this regard, Rubacka et al [57], examining the specific association of PTSD cluster symptoms (re-experiencing, avoidance, and hyperarousal) and MDD in a sample of mothers directly exposed to the WTC attacks, showed that only higher arousal symptom scores were significantly correlated with persistent MDD. Furthermore, if we compare the rates of MDD and PTSD found in some reviewed reports, we can reach some interesting conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Sharp & Harvey propose in their model that depression is one of seven mechanisms that may exacerbate and maintain PTSD and chronic pain. There is also some evidence that arousal may play an important role in persistent depression (Rubacka et al 2008). Bair et al 2003 ;Beesdo et al 2009), depression and PTSD (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Roth et al 2008) is well substantiated. There is also some evidence that arousal may play an important role in persistent depression (Rubacka et al 2008). Future research on PTSD and pain should, therefore, include depression to investigate possible moderating or mediating relationships.…”
Section: Discussionmentioning
confidence: 99%